2019
DOI: 10.1101/718593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid resistance to pesticide control is predicted to evolve in an invasive fish

Abstract: Xenobiotic resistance is commonly found in species with short generation times such as bacteria, 1 annual plants, and insects. Nevertheless, the fundamental evolutionary principles that govern the 2 spread of resistance alleles hold true for species with longer generation times. One such example 3 could occur with sea lamprey (Petromyzon marinus), a parasitic invasive species in the 4 Laurentian Great Lakes that decimated native fish populations prior to its control with the 5 pesticide 3-trifluoromethyl-4-nit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…It may only be a matter of time before further mutations or a continued response to selection allows individuals to survive higher concentrations of TFM. In fact, recent modeling efforts have revealed that given the estimated strength of selection imposed by lamprey control, full‐fledged resistance to TFM is predicted to occur within the next tens of years (Christie et al, 2019). Because of the high gene flow and lack of population structure found throughout the Great Lakes, fully resistant individuals may already be spreading throughout the population even though it may take many more years for successful detection (Christie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It may only be a matter of time before further mutations or a continued response to selection allows individuals to survive higher concentrations of TFM. In fact, recent modeling efforts have revealed that given the estimated strength of selection imposed by lamprey control, full‐fledged resistance to TFM is predicted to occur within the next tens of years (Christie et al, 2019). Because of the high gene flow and lack of population structure found throughout the Great Lakes, fully resistant individuals may already be spreading throughout the population even though it may take many more years for successful detection (Christie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent modeling efforts have revealed that given the estimated strength of selection imposed by lamprey control, full‐fledged resistance to TFM is predicted to occur within the next tens of years (Christie et al, 2019). Because of the high gene flow and lack of population structure found throughout the Great Lakes, fully resistant individuals may already be spreading throughout the population even though it may take many more years for successful detection (Christie et al, 2019). From a pragmatic standpoint, the detection of incipient resistance (IR) means that the development of alternative control measures and the implementation of adaptive management strategies focusing on delaying resistance should be a priority for the continued control of invasive sea lamprey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations